Association Between Urinary Epidermal Growth Factor and Renal Prognosis in Lupus Nephritis. Issue 2 (12th January 2021) - Mejia‐Vilet, Juan M.; Shapiro, John P.; Zhang, Xiaolan L.; Cruz, Cristino; Zimmerman, Grant; Méndez‐Pérez, R. Angélica; Cano‐Verduzco, Mayra L.; Parikh, Samir V.; Nagaraja, Haikady N.; Morales‐Buenrostro, Luis E.; Rovin, Brad H.
Abstract : Objective: To evaluate the role of urinary epidermal growth factor (EGF) as a biomarker of chronic kidney damage in lupus nephritis (LN). Methods: A proteomics approach was used to identify urinary EGF as a biomarker of interest in a discovery cohort of patients with LN. The expression of urinary EGF was characterized in 2 large multiethnic LN cohorts, and the association between urinary EGF levels at the time of flare and kidney outcomes was evaluated in a subset of 120 patients with long‐term follow‐up data. For longitudinal studies, the expression of urinary EGF over time was determined in 2 longitudinal cohorts of patients with LN from whom serial urine samples were collected. Results: Discovery analysis showed the urinary EGF levels as being low in patients with active LN (median peptide count 8.4, interquartile range [IQR] 2.8–12.3 in patients with active LN versus median 48.0, IQR 45.3–64.6 in healthy controls). The peptide sequence was consistent with that of proEGF, and this was confirmed by immunoblotting. The discovery findings were verified by enzyme‐linked immunosorbent assay. Patients with active LN had a significantly lower level of urinary EGF compared to that in patients with active nonrenal systemic lupus erythematosus (SLE), patients with inactive SLE, and healthy kidney donors (each P < 0.05). The urinary EGF level was inversely correlated with the chronicity index of histologic features assessed in kidney biopsy tissue (Spearman's r = −0.67, P < 0.001). Multivariate survival analysis showed that the urinary EGF level was associated with time to doubling of the serum creatinine level (DSCr), a marker of future end‐stage kidney disease (ESKD) (hazard ratio 0.88, 95% confidence interval 0.77–0.99, P = 0.045). Patients whose LN symptoms progressed to DSCr and those who experienced progression to ESKD had a lower urinary EGF level at the time of flare, and urinary EGF levels decreased over the 12 months following flare. All patients who experienced progression to ESKD were identified based on a urinary EGF cutoff level of <5.3 ng/mg. Conclusion: Urinary EGF levels are correlated with histologic kidney damage in patients with LN. Low urinary EGF levels at the time of flare and decreasing urinary EGF levels over time are associated with adverse long‐term kidney outcomes.